Addressing overuse and overdiagnosis in colorectal cancer screening for average-risk individuals. (February 2015) - Garcia, Montse
SUMMARY : Inappropriate screening harms healthy individuals and squanders precious resources. The purpose of this review is to address harms of colorectal cancer screening derived from overuse and overdiagnosis in average-risk individuals. Overuse is associated with shorter than recommended repeat screening and surveillance intervals, and screening in individuals who would not derive benefit because of advanced age or significant comorbidity. Overuse can unnecessarily increase patient harm from overdiagnosis or colonoscopy complications as well as gastroenterologist workload and healthcare costs. There is no evidence to suggest that overdiagnosis is an issue for colorectal cancer screening. However, targeting on cancer prevention (detection of adenomatous polyps) rather than early detection will lead to overdiagnosis as only a small minority of polyps develop into cancer.